KORRUPSIYA UNING KELIB CHIQISH SABABLARI VA UNGA QARSHI KURASHISHDA SINGAPUR STRATEGIYASINING AHAMIYATI (Archive of Conferences, 2021)
The article discusses the causes of corruption flour and Singapore in the fight against itabout the experience of the state and the fight against corruption in our country